Using foresight in times of uncertainty : Analysing interpretative structures in migration-related policy foresight - Suomalainen, Kaisa-Maria (My University, 2024)
The goal of this master's thesis is to explore and analyze interpretative structures in migration-related policy-foresight. Drawing from the conceptualization of foresight as a system, I decided to focus on the individual foresight actors and their experiences with foresight. For this purpose, I interviewed foresight actors in the Finnish ministries and government agencies. My research stance and data collection were inductive, which led me to focus on different approaches and motivations for foresight. During the analysis stage, the thematization was driven by the data, after which existing research findings and relevant theory were used to refine the analysis. The results show the multitude purposes and approaches for migration-related policy foresight. The identified foresight purposes include 1) Supporting preparedness, 2) Internal resource planning, 3) Enabling participation, 4) Fostering capability development, 5) Contributing to organizational strategy, 6) Contributing to society through policy visioning. This range of purposes indicates that the motivations for foresight are varied. In addition to this, different foresight approaches were analyzed. As a result, five different perspectives to foresight were identified. These included 1) Foresight as estimating probable developments, 2) Foresight as exploration of alternative futures 3) Foresight as future-oriented experimentations, 4) Foresight as critical examination of complex phenomena 5) Foresight as anticipating uncertainties. These results suggest that foresight approaches contain a lot of nuance. The results also indicate that the migration-related policy foresight actors have different approaches to foresight, which is reflected in the consideration of relevant foresight capabilities and in their motivation for foresight. The results from this exercise could be used to develop foresight capabilities, and open up discussion about the most potential combinations between different approaches of foresight and foresight purposes. Furthermore, this thesis provides relevant knowledge for prioritizing the goals and means for foresight in the setting of migration policy foresight.

Tässä tulevaisuudentutkimuksen pro gradu -työssä tarkasteltiin valtionhallinnon ennakointitoimijoiden tapoja jäsentää ennakointityötä maahanmuuton kontekstissa. Tutkimuksen fokus oli ennakoinnille annetuissa merkityksissä ja tulkinnoissa, joita analysoitiin aineistolähtöisesti teemoittelemalla. Maahanmuuttoon liittyvässä ennakoinnissa tunnistettiin runsaasti erilaisia lähtökohtia ja näkökulmia. Keskeisemmät tehtävät liittyivät ennakointiin hyödyntämiseen valmiustyössä sekä sisäisessä suunnittelussa. Lisäksi esille nousivat osallisuuteen ja osaamisen kehittämiseen liittyvät tavoitteet. Ennakoinnin merkitystä pidettiin tärkeänä myös strategisen kehittämisen ja yhteiskunnallisen visioinnin tavoitteiden kannalta. Ennakointia jäsennettiin eri näkökulmista, jotka liittyivät todennäköisten kehityskulkujen ennakointiin, vaihtoehtoisten tulevaisuuksien avaamiseen, kokeelliseen ennakointiin, ennakointiin ilmiöiden kriittisenä tarkasteluna sekä epävarmuuksien tunnistamiseen. Tutkimuksen tuloksia voidaan hyödyntää ennakointikyvykkyyden, organisaatioiden sisäisen ennakointitoiminnan sekä kansallisen ennakointityön kehittämisessä
Keywords: policy foresight, foresight, frames, uncertainty, migration